儒道死亡思想之比較: A Comparison of the Confucian and Daoist Views on Death - JIN, Fenglin (International Journal of Chinese & Comparative Philosophy of Medicine, 1999)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 本文對儒道死亡思想進行了深入細緻的比較研究，認為在對待死亡的態度上，儒家重生輕死，對死存而不論；道家則由反對悅生惡死，進而歌頌、讚美死亡。在對死亡本質的認識上，儒家從天命角度出發，認為死由命定，是天意的體現；道家則認為死是氣聚氣散的結果；同時二者又都認為死亡本質上是一種安息。在對待死亡價值問題上，儒家強調把死亡落實到道德價值的開拓上；而道家則堅決反對給死亡以價值判斷，強調避死全身才是人生之根本。在超越死亡的途徑上，儒家認為人只要生治充實，為理想而奮鬥，創造了某種永恆之物，便可超越死亡；而道家則強調通過，“心齋”、“坐忘”，達到與大道合一，從而實現死而不亡。儒進上述對死亡及死後狀態的體認，派生出積極入世、奮發有為和純精神修練、不問世事的截然不同的人生態度和準則，對中國的後世哲學產生了重大而深遠的影響。 This essay is a comparative and in-depth analysis of the Classical Confucian (Confucius, Mencius) and Classical Daoist (Lao Zi, Zhuang Zi) views on death. Four aspects of these two philosophies of death (attitude toward death, philosophical articulation of the essence of death, valuation of death, and transcending death) are analyzed and critically contrasted. First, regarding the general attitude toward death, Confucianism is more rational whereas Daoism is more mystical. Confucianism deems that the problem of human life is more important than the problem of human death, and hence speaks little of death. Daoism, however, is strongly against the human tendency to avoid the topic of death. Since human life and human death alternates like the four seasons, death should by no means be detested. On the contrary, death should be greeted with enthusiasm. Concerning the nature of death, Confucianism deems that death is a manifestation of the decree of Heaven, which is beyond our control. Death is fate, and is not subject to our autonomy. Daoism understands life and death in terms of the presence and the dispersion of qi (vital force), which is also beyond human control. Besides, both philosopies concur that death is the time of rest；it is a release from the labor of this world. Regarding the value of death, Confucianism strongly thinks that death, like life itself, should be used to serve the cause of ren and yi (i.e., morality). Hence death can be potentially full of moral significance, and we should try our best to give as much moral meaning to it as possible. We therefore should be prepared to give up our life for the sake of a moral cause. Daoism strongly disagrees with Confucianism in this regard, and takes a naturalistic stance toward death. Since death is an intrinsic part of life, it should neither be delayed nor hastened. Life should be lived to its temporal fullness and should not be sacrificed for any human cause. To die for morality is as bad as to die for financial gain. Lastly, both Confucianism and Daoism try to transcend the negation and annihilation imposed by death. Confucianism thinks that as long as we live altruistically we will not be bothered by death and not be affected by the anxiety over death. Besides, though one's biological life will perish, one can attain immortality through one's lasting influence to subsequent generations. Daoism, on the other hand, emphasizes the importance of being one with the Dao through meditation and other spiritual disciplines. The end result will be a total mindlessness of death. DOWNLOAD HISTORY | This article has been downloaded 36 times in Digital Commons before migrating into this platform.